Historia startów klubów bydgoskich w I lidze szachowej w latach 1949-2012 (Kronika Bydgoska, 2013)
The task of the Polish Team chess championship (first chess league) was to select the strongest club in Poland. The first club games took place in the year 1949. In the years 1949-2012, the first league included 5 Bydgoszcz teams: Spójnia Bydgoszcz, Budowlani Bydgoszcz, Caissa Bydgoszcz, Łączność Bydgoszcz, and Chemik Bydgoszcz. The record holder in the number of starts in the above-named period was the club Chemik Bydgoszcz, which was in the group of the best teams in Poland continuously for 10 years. Bydgoszcz teams won in total 6 medals, including 1 gold medal (Łączność Bydgoszcz, 1978), 1 silver (Chemik Bydgoszcz, 1984) and 4 bronze medals (Spójnia Bydgoszcz, 1952, Łączność Bydgoszcz, 1974 and Chemik Bydgoszcz, 1982 and 1983). In the years 1949-2012, Bydgoszcz clubs occupied all places on the podium. Łączność Bydgoszcz in the years 1972-1982, Chemik Bydgoszcz in the years 1982-1996, and Budowlani Bydgoszcz in the years 1957-1959 occupied the top position in the national chess arena. Starting from 1996, no Bydgoszcz club participated in team games for the Polish championship. They have been experiencing a period of stagnation to this day.